Creative transformations in visual arts of early french modernism: treatment of nude body - Juzefovič, Agnieška (Creativity Studies, 2016)
Resent paper is focused on the early modern culture, particularly on the topic of visual art and its confrontation with traditional, pre-modern culture and aesthetic. The author unveils how and why painters of early French modernism had rejected traditional representation of eroticism, typical for pre-modern art, especially for the art of academicism. Thus from their artworks disappeared sublimated, exalted nudity, withdrew nudes modestly hidden under mythological or religious context. In the works of impressionists and postimpressionists naked body was depicted frankly, openly, without any excuse of what was supposed to be decent. Such were the nude women of paintings of Auguste Manet and Amedeo Modigliani who present merely their femininity and sexuality, while symbolizing the liberation from moral norms and heralding sexual revolution of the 20th century. Relaxed, healthy, pink-cheeked girls in Pierre-Auguste Renoir’s paintings spread subtle eroticism and the mood of joyful life. Life of Parisian cabarets and brothels come alive through naked or semi-naked female figures which on Henri de Toulouse-Lautrec and Edgar Degas canvases seem as if they are unaware of being watched. Nude bodies in the paintings of such French post-impressionists like Henri Matisse and Paul Gauguin were depicted in exotic, oriental ambience and referred to the philosophical background of romanticism. Paul Cézanne’s nudes particularly his famous scenes with bathers disclose essential aims of this painter – to reach the essence of the very thing. Transformations of the treatment of nude body by early French modernists help to understand general context of creative changes in visual arts on the edge of the 19th and 20th centuries.